RETRACTED: IP1867B suppresses the Insulin-like Growth Factor 1 Receptor (IGF1R) ablating Epidermal Growth Factor Receptor inhibitor resistance in adult high grade gliomas. (28th August 2019) - Mihajluk, K.; Simms, C.; Reay, M.; Madureira, P.A.; Howarth, A.; Murray, P.; Nasser, S.; Duckworth, C.A.; Pritchard, D.M.; Pilkington, G.J.; Hill, R.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). This article has been retracted at the request of the Editor-in-Chief due to concerns regarding the legitimacy of images and data presented in the paper. Though a corrigendum (Can. Lett. Vol. 469, 2020, pages 524-535) was previously published to address some of these concerns, this corrigendum has also been found to contain errors and therefore cannot stand. Specific concerns are listed below. The Editor and Publisher received a letter from the University of Portsmouth alerting us to an investigation into alleged research misconduct. The University concluded their investigation with external experts and determined that misconduct did take place in relation to the research involved in this paper. Upon our separate investigation, it has been determined that the paper headline relies on showing that there was considerable reduction of IGF1R, IL6R and EGFR post treatment in all cell lines. During review, it was determined that this cannot be concluded from the presented data. For example, in SEBTA-003 the EGFR levels go up and there is no difference in IGFR1. It is apparent from Fig 4d that in the SEBTA-003 cell line the EGFR level does not go down, which is stated in the Results section on page 32, it is rather going up. The data for IGFR1 are inconclusive and there are concerns regarding the blot. The general implications would be that the effects of the drug IP1867B does not seem to be the same for all tested cell lines, and this should have been discussed in detail by the authors. Additionally, in subsequent experiments (Fig. 4g and h) the SEBTA-003 cell line (no reduction of EGFR, rather increased expression) and the other 3 cell lines (reduction of EGFR) show similar responses. This is particularly evident in Fig. 4g: Two cell lines are compared, SEBTA-003 (increased EGFR expression) and UP-029 (decreased EGFR expression), both behave similarly after exposure to drugs. The corrigendum (https://doi.org/10.1016/j.canlet.2019.10.002 ) issue is with respect to the Supplemental Figure 6i EGFR, particularly panel IP1867B. The Corrigendum states that the left part is a cut out of the very right part. If so, the bands for IP1867B should show the same staining pattern - but they do not. Also, in the Corrigendum, there are incorrect mentions between day 14 in the Figure and day 19 in the Figure legend. All authors were informed of the retraction in advance. Drs. Pritchard and Duckworth agreed to the retraction. The corresponding author, Dr Hill, did not agree to the retraction. No response had been received from Drs. Mihajluk, Simms, Reay, Madureira, Howarth, Murray, Nasser and Pilkinton at the time of the retraction being published.